EFFECT OF ADDING DIFFERENT LEVELS OF FLAXSEED OIL TO DIETS ON EJACULATE VOLUME AND SPERM CONCENTRATION IN SEMEN IN OSTRICHES - Ali, Nashwan Majeed (PT. Antis International Publisher, 2025)
Objective: This study aimed to investigate the impact of dietary supplementation with flaxseed oil on the morphological characteristics of semen in male ostriches. Method: The experiment was conducted at the Babylon Reserve for Ostrich, Falcon, and Deer Breeding, Babylon Province, Iraq, using 27 sexually mature ostriches divided into three treatment groups with three replicates each, organized under a family-based system (two females and one male per replicate). Birds were housed in specialized pens, with males separated from females from the beginning of the trial, and all were provided a standardized diet containing 17.34% crude protein and 2740.56 kcal/kg metabolizable energy. Treatments included a control diet and diets supplemented with 1% or 2% flaxseed oil. Semen traits assessed included ejaculate volume, sperm concentration, and packed sperm volume. Results: Supplementation with flaxseed oil at both inclusion levels led to statistically significant and highly significant improvements in most evaluated semen parameters compared with the control. Novelty: These findings provide new evidence that flaxseed oil, as a rich source of Omega-3 fatty acids, can enhance reproductive performance in male ostriches, offering a natural nutritional strategy to improve fertility and productivity in ostrich farming systems.